2011
DOI: 10.1007/dcr.0b013e3181f4737e
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Rectopexy for Complex Rectocele: A Prospective Comparison of Short-Term Outcomes

Abstract: In our experience, the robotic approach for the treatment of complex rectocele is as safe as the laparoscopic approach, with favorable short-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 15 publications
(21 reference statements)
7
60
1
Order By: Relevance
“…In the long run, approximately 80 % of patients with ODS and intussusception would benefit from LVMR [5]. The present results are in line with previously reported functional outcomes, although different scoring systems were used for their assessment [10,11]. The symptom relief was significant in questions assessing ODS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the long run, approximately 80 % of patients with ODS and intussusception would benefit from LVMR [5]. The present results are in line with previously reported functional outcomes, although different scoring systems were used for their assessment [10,11]. The symptom relief was significant in questions assessing ODS.…”
Section: Discussionsupporting
confidence: 81%
“…It is mainly indicated to treat rectal prolapse [5,6], but lately it has also been offered to selected patients with internal rectal prolapse and complex rectocele, and has shown improved functional results [7][8][9][10][11]. LVMR provides an option to correct middle and posterior compartment procidentia at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the technical feasibility and equivalence of ventral mesh rectopexy for treating complex rectocoele using either the laparoscopic or roboticassisted approach [18]. The aim of this paper was thus to focus on the function of a consecutive series of patients with complex rectocoele operated on using the Da Vinci-SÔ robotic system or by conventional laparoscopy, by assessing for anatomical recurrence and changes in functional symptom scores.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited literature on robotic rectopexy for rectal prolapse. Several studies reported significantly longer operative times for robotic rectopexy as compared with laparoscopic rectopexy [42,53,54]. Mean operative time ranged from 152 to 221 minutes as compared with a range of 113 to 163 minutes, respectively.…”
Section: Rectopexymentioning
confidence: 97%